The Role of Herpes Viruses in Pulmonary Fibrosis - Duckworth, Anna; Longhurst, Hilary J.; Paxton, Jane K.; Scotton, Chris J. (Frontiers in Medicine, 2021)
Pulmonary fibrosis (PF) is a serious lung disease which can result from known genetic or environmental exposures but is more commonly idiopathic (IPF). In familial PF (FPF), the majority of identified causal genes play key roles in the maintenance of telomeres, the protective end structures of chromosomes. Recent evidence suggests that short telomeres may also be implicated causally in a significant proportion of idiopathic cases. The possible involvement of herpes viruses in PF disease incidence and progression has been examined for many years, with some studies showing strong, statistically significant associations and others reporting no involvement. Evidence is thus polarized and remains inconclusive. Here we review the reported involvement of herpes viruses in PF in both animals and humans and present a summary of the evidence to date. We also present several possible mechanisms of action of the different herpes viruses in PF pathogenesis, including potential contributions to telomere attrition and cellular senescence. Evidence for antiviral treatment in PF is very limited but suggests a potential benefit. Further work is required to definitely answer the question of whether herpes viruses impact PF disease onset and progression and to enable the possible use of targeted antiviral treatments to improve clinical outcomes.